Sulfur and selenium doped nickel chalcogenides as efficient and stable electrocatalysts for hydrogen evolution reaction: The importance of the dopant atoms in and beneath the surface. (August 2020) - Liu, Tengyi; Diao, Peng; Lin, Zheng; Wang, Hailiang
Abstract: Doping is an efficient strategy to enhance the activity of electrocatalysts. This work is aimed at (1) exploring the effect of surface- and bulk-doping on the activity of nickel chalcogenides (NCs) for hydrogen evolution reaction (HER), and (2) developing highly efficient NCs for HER. To these ends, we first prepared nickel foam (NF) supported Ni3 Se4 and Ni3 S2, and then superficially doped them with S and Se, respectively, via a facile hydrothermal anion exchange reaction. We demonstrated by experiments and density functional theory (DFT) calculations that the surface-only-doping significantly improved the activity of NCs for HER. DFT calculations also reveal that, for bulk-doped NCs, the dopant atoms beneath the surface also contribute significantly to the activity. Inspired by this result, we developed a one-step hydrothermal method to prepare the bulk-doped NC hybrid, which exhibited a high activity for HER with an onset overpotential of 32 mV, an exchange current density of 0.48 mA cm −2, and a Tafel slope of 61 mV dec −1 . The overpotentials required to produce HER current densities of 10, 20, 50 and 100 mA cm −2 are only 89, 107, 128 and 138 mV, respectively, with an excellent stability and a nearly 100% Faraday efficiency. This HER performance is superior to most NC catalysts reported so far in literature. Graphical abstract: Dopant atoms both in and beneath the surface contribute greatly to the activity of doped nickel chalcogenides for hydrogen evolution reaction (HER), and the hybrid composed of bulk-doped S–Ni3 Se4 and Se–Ni3 S2 exhibits an excellent HER performance. Image 1 Highlights: Surface-only-doped nickel chalcogenides (s-S-Ni3 Se4 and s-Se-Ni3 S2 ) were prepared for the first time. Surface doping significantly improves the activity of s-S-Ni3 Se4 and s-Se-Ni3 S2 for HER. DFT calculations reveal that dopant atoms both in and beneath the surface contribute to the activity. Bulk-doped S–Ni3 Se4 and Se–Ni3 S2 hybrid exhibits an HER activity superior to most nickel chalcogenides. This work sheds light on how the dopants atoms in and beneath the surface influence the activity for HER.